Neuroprotective effects of interleukin 10 in spinal cord injury - Li, Juan; Wang, Pei; Zhou, Ting; Jiang, Wenwen; Wu, Hang; Zhang, Shengqi; Deng, Lingxiao; Wang, Hongxing (Frontiers in Molecular Neuroscience, 2023)
Spinal cord injury (SCI) starts with a mechanical and/or bio-chemical insult, followed by a secondary phase, leading progressively to severe collapse of the nerve tissue. Compared to the peripheral nervous system, injured spinal cord is characterized by weak axonal regeneration, which leaves most patients impaired or paralyzed throughout lifetime. Therefore, confining, alleviating, or reducing the expansion of secondary injuries and promoting functional connections between rostral and caudal regions of lesion are the main goals of SCI therapy. Interleukin 10 (IL-10), as a pivotal anti-inflammatory and immunomodulatory cytokine, exerts a wide spectrum of positive effects in the treatment of SCI. The mechanisms underlying therapeutic effects mainly include anti-oxidative stress, limiting excessive inflammation, anti-apoptosis, antinociceptive effects, etc. Furthermore, IL-10 displays synergistic effects when combined with cell transplantation or neurotrophic factor, enhancing treatment outcomes. This review lists pleiotropic mechanisms underlying IL-10-mediated neuroprotection after SCI, which may offer fresh perspectives for clinical translation.